2015
DOI: 10.1159/000369684
|View full text |Cite|
|
Sign up to set email alerts
|

Inflammatory Cytokine TSLP Stimulates Platelet Secretion and Potentiates Platelet Aggregation via a TSLPR-Dependent PI3K/Akt Signaling Pathway

Abstract: Aims: Thymic stromal lymphopoietin (TSLP) plays an important role in inflammatory diseases and is over-expressed in human atherosclerotic artery specimens. The present study investigated the role of TSLP in platelet activation and thrombosis models in vitro and in vivo, as well as the underlying mechanism and signaling pathway. Methods and Results: Western blotting and flow cytometry demonstrated that the TSLP receptor was expressed on murine platelets. According to flow cytometry, platelet stimulation with TS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…Thrombin-mediated platelet activation is associated with rapid depolymerization of F-actin prior to the release of Ca 2+ from intracellular stores and the induction of Ca 2+ entry [24]. Platelet activation and migration as well as thrombus formation are related to PI3K/Akt signaling [25][26][27]. We and others have reported that PI3K-mediated stimulation of platelets through the TRPC6 channel is involved in platelet activation in diabetic patients [2,28].…”
Section: Discussionmentioning
confidence: 98%
“…Thrombin-mediated platelet activation is associated with rapid depolymerization of F-actin prior to the release of Ca 2+ from intracellular stores and the induction of Ca 2+ entry [24]. Platelet activation and migration as well as thrombus formation are related to PI3K/Akt signaling [25][26][27]. We and others have reported that PI3K-mediated stimulation of platelets through the TRPC6 channel is involved in platelet activation in diabetic patients [2,28].…”
Section: Discussionmentioning
confidence: 98%
“…Chorein has previously been shown to interact with PI3K [1,2], which is known to participate in the regulation of degranulation in a wide variety of cells [32,33,34,35,36,37,38,39,40]. Possibly, chorein similarly modifies degranulation of those cells.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorophore-labeled antibodies were utilized for the detection of P-selectin expression (Wug.E9-FITC) [33] and the active form of α IIb β 3 integrin (JON/A-PE) [34]. Washed mouse platelets (1x10 6 ) were suspended in modified Tyrode buffer (pH 7.4) containing 1 mM CaCl 2 and antibodies (1: 10 dilution) and subsequently subjected to the respective treatments and for the indicated time periods at room temperature (RT).…”
Section: Methodsmentioning
confidence: 99%